Singapore grassroots movement unearthed : why do they serve? - Ching, Darren Wee Heng (Nanyang Technological University, 2020)
The grassroots scene in Singapore is not unheard of but its strucutre and numerous committees within have often been confusing for the average Singaporean to understand. What is the role of the People's Association (PA) in SIngapore's grassroots movement?